2019
DOI: 10.1177/0306624x19845784
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Confidence in Media and Criminal Justice Institutions

Abstract: In every society, the main purpose of the criminal justice system is to maintain social order and ensure that citizens comply with the law. To do this effectively, the police and court systems need citizen cooperation and obedience, and willingness to assist with criminal investigations and report crimes to the police. The purpose of this study is to examine the association between confidence in the media and confidence in the criminal justice institutions in South Africa. The study tests two objectives: to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Citizens' who expressed high trust in the media, indicated that institutions in Brazil are legitimate, court is fair, and reported high trust in the police. This observation is consistent with prior efforts that have examined the relationship between the two variables in Africa (Boateng & Kaiser, 2019) and Asia (Leechaianan et al, 2012;Wu, 2014). Assumptions from the cognitive response theory provide a perfect explanation for this behavior in Brazil.…”
Section: Discussionsupporting
confidence: 89%
“…Citizens' who expressed high trust in the media, indicated that institutions in Brazil are legitimate, court is fair, and reported high trust in the police. This observation is consistent with prior efforts that have examined the relationship between the two variables in Africa (Boateng & Kaiser, 2019) and Asia (Leechaianan et al, 2012;Wu, 2014). Assumptions from the cognitive response theory provide a perfect explanation for this behavior in Brazil.…”
Section: Discussionsupporting
confidence: 89%
“…These findings support the paramount importance of trust as a feature of the WA in a mandated context (Menger, 2018). However, it should be noted that – while it is indeed built within a specific WA – trust remains a complex concept that is influenced by many factors; for example, personal experiences or the experiences or significant others (Fagan and Tyler, 2005) and cultural background (Boateng and Kaiser, 2019).…”
Section: The Working Alliance (Wa) Between Justice Assistants and Thementioning
confidence: 99%
“…Individuals utilize vicariously gathered information to evaluate law enforcement legitimacy (Perry et al, 2019). Therefore, citizens who do not have contact with courts, the criminal justice system, or law enforcement must consider what other factors might influence their confidence in the criminal justice system (Boateng & Kaiser, 2019). People who never or rarely engage with law enforcement officers can shape their perspectives of police from what they have seen in the media.…”
Section: Introductionmentioning
confidence: 99%
“…People gain their knowledge of social reality from four sources: social groups or institutions (schools or churches), the media, significant others (family and friends), and personal experiences (Alitavoli & Kaveh, 2018;Boateng & Kaiser. 2019).…”
Section: Introductionmentioning
confidence: 99%